Preliminary data on Brachyura (Crustacea) in coastal mangrove forests from Tinh Gia (Thanh Hoa province) to Hoi An (Quang Nam province) - Nhuong, Do Van; Khac, Hoang Ngoc (Academia Journal of Biology, 2006)
The surveying on Brachyura (Crustacea) in coastal mangrove forests from Tinhgia (Thanhhoa province) to Hoian (Quangnam province) was carried out in December, 2003 at 9 localities. 36 crab species, belonging to 5 families were collected and the species number was mainly in the families Ocypodidae and Grapsidae. In addition, there were several wide range species found in the northern fauna as well as in the southern fauna of Vietnam. Crabs were numerous in species in Vietnam mangrove ecosystems. The characteristics of the crab species composition in mangrove forests from Tinhgia to Hoian were following species: Parapyxidognathus deianira, Hemigrapsus penicillatus, Neoepisesarma lafondi, Scopimera curtelsoma, Ocypode sinensis and Metopograpsus thukuhar. All the crab species found in these mangrove stands were burrowers and ground-dwelling animals. The ground-dwelling crabs could be found on the lower parts of the tree trunks.